2018
DOI: 10.1111/jgs.15280
|View full text |Cite
|
Sign up to set email alerts
|

Lumbopelvic Pain and Threats to Walking Ability in Well‐Functioning Older Adults: Findings from the Baltimore Longitudinal Study of Aging

Abstract: LPP was common in well-functioning older adults and was associated with greater energetic cost of walking and poorer perceived and observed walking endurance. The longitudinal effect of LPP is unclear, but worsening perception of walking ability and its contribution to future mobility loss warrants further attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In a previous study from the BLSA, Simonsick et al [26] observed that time to walk 400m, the measure termed endurance performance in this study, was slower with greater lumbopelvic pain severity experienced in the prior year. Our study demonstrated that other objectivelymeasured physical function components were also associated with non-chronic LBP intensity (ExSPPB, usual gait speed, total standing balance, and high fatigability), suggesting that more intense pain is associated with poorer performance of the activities that do not directly engage trunk movements.…”
Section: Plos Onesupporting
confidence: 48%
See 1 more Smart Citation
“…In a previous study from the BLSA, Simonsick et al [26] observed that time to walk 400m, the measure termed endurance performance in this study, was slower with greater lumbopelvic pain severity experienced in the prior year. Our study demonstrated that other objectivelymeasured physical function components were also associated with non-chronic LBP intensity (ExSPPB, usual gait speed, total standing balance, and high fatigability), suggesting that more intense pain is associated with poorer performance of the activities that do not directly engage trunk movements.…”
Section: Plos Onesupporting
confidence: 48%
“…Intensity was analyzed as a continuous variable [ 25 ]. Participants that reported moderate to severe pain (rated >4) of any type during their pre-visit screen were encouraged to postpone their clinic visit to minimize potential interferences in the performance of physical functioning tests [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…with the answer options "Yes," "No," and "I don't know." Among those who answer "Yes" for the previous question, the intensity (0-10 scale, 0 = no pain, 10 = extremely intense pain) and duration [longest consecutive time period (weeks)] of low back pain will be evaluated (59). The Brazilian version of the Roland Morris functionality questionnaire, which includes 24 items (yes or no) on physical disability caused by back pain, will also be applied.…”
Section: Low Back Painmentioning
confidence: 99%
“…For example, the Indonesian Family Life Survey comprising of adults aged at least 50 years found that participants who reported severe pain had higher functional limitation scores and weaker grip strength [ 24 ], while another study found that pain severity was associated with activities of daily living limitations [ 3 ]. Notably, for certain painful conditions, such as lumbopelvic pain, higher levels of pain severity negatively impacted walking ability [ 25 ].…”
Section: Discussionmentioning
confidence: 99%